Can Music Foster Learning – Effects of Different Text Modalities on Learning and Information Retrieval - Lehmann, Janina A. M.; Seufert, Tina (Frontiers in Psychology, 2018)
This study investigates the possibilities of fostering learning based on differences in recall and comprehension after learning with texts which were presented in one of three modalities: either in a spoken, written or sung version. All three texts differ regarding their processing, especially when considering working memory. Overall, we assume the best recall performance after learning with the written text and the best comprehension performance after learning with the sung text, respectively compared to both other text modalities. We also analysed whether the melody of the sung material functions as a mnemonic aid for the learners in the sung text condition. If melody and text of the sung version are closely linked, presentation of the melody during the post-test phase could foster text retrieval. 108 students either learned from a sung text performed by a professional singer, a printed text, or the same text read out loud. Half of the participants worked on the post-test while listening to the melody used for the musical learning material and the other half did not listen to a melody. The written learning modality led to significantly better recall than with the spoken (d = .97) or sung text (d =.78). However, comprehension after learning with the sung modality was significantly superior compared to when learning with the written learning modality (d = .40). Reading leads to more focus on details, which is required to answer recall questions, while listening fosters a general understanding of the text, leading to higher levels of comprehension. Listening to the melody during the post-test phase negatively affected comprehension, irrespective of the modality during the learning phase. This can be explained by the seductive detail effect, as listening to the melody during the post test phase may distract learners from their main task. In closing, theoretical and practical implications are discussed.